Jenis-Jenis Anak Berkebutuhan Khusus (ABK) I: Tunanetra, Tunarungu, Tunagrahita, Tunadaksa, Tunalaras dan Tunawicara (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2025)
This article aims to describe various types of children with special needs (CwSN) along with their characteristics, needs, and appropriate educational approaches. Employing a library research method, this study analyzes scientific literature concerning six categories of CwSN: visual impairment, hearing impairment, intellectual disability, physical disability, emotional-behavioral disorders, and speech impairment. The findings reveal that each category possesses distinct challenges and potentials, requiring adaptive and comprehensive educational services. Children with visual impairment need alternative visual support, those with hearing impairment require communication aids such as sign language, children with intellectual disabilities need simplified and structured learning strategies, while those with physical disabilities require physical assistance and therapy. Meanwhile, children with emotional-behavioral disorders benefit from behavioral and emotional guidance, and children with speech impairment require speech therapy and communication aids. The study also emphasizes the importance of accurate assessment and the application of individualized, multisensory, therapeutic, and inclusive learning approaches to optimize students’ development. This article highlights that comprehensive understanding of CwSN diversity is essential for implementing effective and equitable inclusive education.